Impuesto a las embarcaciones de recreo - Ruiz de Castilla Ponce de León, Francisco J. (Pontificia Universidad Católica del Perú, 2013)
Tax Law attempts to regulate the majority of possible circumstances, in order to achieve an effective taxing on what requires be taxed. Being the acquisition of recreational boats an increasingly frequent phenomenon, it’s necessary to apply the Tax to Recreational Boats and to understand this tax in the light of the Peruvian legislation. On this occasion, the author analyzes the current situation of the imposition to these movable goods, through the interpretation and even questioning of its legal basis: the Law of Municipal Taxation and the regulation of the Tax to Recreational Boats.

El Derecho Tributario intenta regular la mayoría de circunstancias posibles para gravar efectivamente aquello que requiera imposición. Siendo la adquisición de embarcaciones de recreo un fenómeno cada vez más frecuente, surge la necesidad de aplicar el Impuestoa las Embarcaciones de Recreo y de entender esta carga a la luz de la normativa peruana. En esta oportunidad, el autor analiza la situación actual de la imposición a estos bienes muebles, a través de la interpretación de su base legal: La Ley de Tributación Municipal yel Reglamento del Impuesto a las Embarcaciones de Recreo.
Keywords: Law; Tax To Recreational Boats; Tax Policy; Wealth Tax; Tax Revenue; Local Governments; Impuesto a las embarcaciones de recreo; Política fiscal; Imposición al patrimonio; Ingreso tributario; Gobiernos locales; https://purl.org/pe-repo/ocde/ford#5.05.01